Enhancing Elementary Students’ Environmental Literacy through an Integrated Contextual Approach: Multimedia Learning Materials, Adiwiyata Values, and Post-Mining Contexts - Ayu Rahayu; Widodo, Sri; Esther Sanda Manapa (International Electronic Journal of Elementary Education, 2026)
Environmental literacy in elementary education is essential because early learning experiences strongly influence students’ long-term environmental knowledge, attitudes, and behavior. However, instructional approaches that integrate digital learning environments, environmental values, and authentic environmental contexts remain limited in elementary environmental education. This study evaluates the effectiveness of the Integrated Contextual Digital Environmental Learning Approach (ICDELA), a framework that integrates multimedia learning, Adiwiyata environmental values, and post-mining environmental contexts to enhance students’ environmental literacy. A quasi-experimental design with a non-equivalent control group was conducted involving 110 fifth-grade students from elementary schools in mining-affected areas of Southeast Sulawesi, Indonesia. Environmental literacy was assessed across three dimensions: environmental understanding, environmental attitude, and pro-environmental behavior. Data were analyzed using paired-sample t-tests, independent-sample t-tests, and Cohen’s d effect size analysis. The results showed that students who participated in the ICDELA approach achieved significantly higher environmental literacy than those in conventional learning. Effect size analysis indicated a large improvement in environmental understanding (d = 0.81) and moderate improvements in environmental attitude (d = 0.54) and pro-environmental behavior (d = 0.52). These findings demonstrate that integrating multimedia learning, environmental values, and contextual environmental issues within a digital learning framework can effectively promote environmental literacy among elementary school students.